Vitamin D in obstructive sleep apnea syndrome follow up and treatment: A study of 482 cases - Ayşe Karaoğullarından; Birgul Tuhanioglu; Sanem Okşan Yılmaz; Zeynel Abidin Erkan (National Scientific Medical Center, 2021)
Aim: The aim of the study was to determine the factors associated with Obstructıve Sleep Apnea Syndrome (OSAS) severity and vitamin D  deficiency by examining routine laboratory parameters in patients with OSAS without comorbidities. We also aimed to see whether the severity of OSAS increased with decreasing levels of vitamin D. Material and Method: Patients who presented to Adana City Training and Research Hospital, Ear Nose Throat Clinic with the symptoms of snoring and sleep apnea and who underwent PSG in the sleep laboratory of the Otorhinolaryngology Clinic were included in the study.  Blood results were analyzed retrospectively from the hospital information system. The patients were divided into groups according to their Apnea hypopnea Index (AHI)  values ​​as simple snoring, mild OSAS, moderate OSAS, and severe OSAS. According to the vitamin D values, the patients; Cathogarized as sufficient> 30 ng / ml, insufficient 20-30 ng / ml and deficient <20 ng / ml. Results: Out of the 777 patients examined 482 patients  fulfilling the inclusion criteria were analysed for the study. It was seen that severity of OSAS increased concomitantly with decreasing Vitamin D levels. Conclusion: Vitamin D deficiency is observed in patients with OSAS and is related to the severity of the disease.  We think that vitamin D therapy may be beneficial in reducing the severity of the disease.